2007
DOI: 10.1080/17290376.2007.9724883
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and measuring AIDS-related stigma in health care settings: A developing country perspective

Abstract: AIDS-related stigma and discrimination remain pervasive problems in health care institutions worldwide. This paper reports on stigma-related baseline findings from a study in New Delhi, India to evaluate the impact of a stigma-reduction intervention in three large hospitals. Data were collected via in-depth interviews with hospital staff and HIV-infected patients, surveys with hospital workers (884 doctors, nurses and ward staff) and observations of hospital practices. Interview findings highlighted drivers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
123
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(146 citation statements)
references
References 13 publications
21
123
1
1
Order By: Relevance
“…Generally, participants acknowledged that the magnitude of stigma and/or discrimination has greatly decreased compared with previous years. As in previous studies (Surlis & Hyde, 2001;Letamo, 2005;Reis et al, 2005;Mahendra et al, 2007;Feyissa et al, 2012;Ekstrand et al, 2013), this study found some variation in the causes of stigma and discrimination in health care settings. It confirms that existing stigma and discrimination in society, transmission-related fear and institutional policies on HIV management, as well as lack of proper knowledge of HIV amongst health care workers not directly involved in the treatment of SSA migrant women with HIV, drive and endorse stigma feelings and discriminatory attitudes.…”
Section: Discussionsupporting
confidence: 76%
“…Generally, participants acknowledged that the magnitude of stigma and/or discrimination has greatly decreased compared with previous years. As in previous studies (Surlis & Hyde, 2001;Letamo, 2005;Reis et al, 2005;Mahendra et al, 2007;Feyissa et al, 2012;Ekstrand et al, 2013), this study found some variation in the causes of stigma and discrimination in health care settings. It confirms that existing stigma and discrimination in society, transmission-related fear and institutional policies on HIV management, as well as lack of proper knowledge of HIV amongst health care workers not directly involved in the treatment of SSA migrant women with HIV, drive and endorse stigma feelings and discriminatory attitudes.…”
Section: Discussionsupporting
confidence: 76%
“…Groups vulnerable to HIV are commonly associated with HIV infection in India which predisposes them to discrimination. A little less than half of all health staff (43%) in a base line survey (Mahendra et al, 2007) for instance, agreed with the statement, 'sex workers are the only women to worry about getting HIV' implying that sex workers are the only women who are vulnerable to HIV because of their risk behaviour.…”
Section: Article Originalmentioning
confidence: 99%
“…HIV status disclosure forms an important theme in many stigma studies. Involuntary disclosure of a person's HIV status in the health setting through health staff is reported to be the beginning of the stigmatisation experience for most positive people in India (Bharat et al, 2001;Elamon, 2005;Paxton et al, 2005;Mahendra, Gilborn, Bharat, Mudoi, Gupta, George et al, 2007). See Box 1.…”
Section: Stigma Themes Based On Qualitative and Mixed Methods Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The health sector has been identified as one of the areas in which discrimination occurs (Mahendra, et al, 2007). Studies have documented negative attitudes to PLWHA in health care settings in Nigeria and elsewhere (Adelekan et al, 1995;Fido & Al Kamezi, 2002;Hentgen, Jaureguiberry, Ramiliarisoa, Andrianantoandro & Belec, 2002;Quach, Mayer, McGarvey, Lurie & Do, 2005;Reis et al, 2005).…”
Section: Introductionmentioning
confidence: 99%